The Exploitation of Women in Marketing Communications: Strategies for Beginner Entrepreneurs in Gender Literacy Social Media Brand - Setiyaningsih, Lian Agustina; Molyo, Priyo Dari; Sulfani, Sulfani (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
This study aims to investigate the exploitation of women in marketing communications and new entrepreneurial strategies for building brand awareness through social media that are more sensitive to gender issues. Social media has become an important platform in marketing communications, enabling customer interaction, building brands, and creating brand awareness. However, there is a phenomenon of exploitation of women in marketing strategies on social media that reinforces gender stereotypes and ignores important issues that affect women. This study uses the literature study method by analyzing 63 journal articles to understand better women's exploitation in business communication and the importance of gender-aware entrepreneurial strategies in building brand awareness through social media. In this study, it was found that novice entrepreneurs must adopt strategies that are gender literate in building brand awareness through social media. This strategy involves using inclusive language, eliminating gender stereotypes in content, and promoting gender equality and diversity in business communications. Through the use of social media that is more sensitive to gender issues, a more inclusive, equal, and fair business environment can be created without reinforcing gender stereotypes and discrimination. Keywords: Exploitation of Women, Social Media, Beginner Entrepreneurs, Brand Awareness.